Improvement of investment support for human capital development in the conditions of digital transformation - Irtyshcheva, Inna; Trushlyakova, Antonina (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The features of investment in the development of human capital in Ukraine at the regional level, in the private sector and at the household level have been investigated. It is noted that the state acts as the main investor in the formation and development of human capital, financing the main expenses in the field of education, medicine, cultural and physical development and social security. However, state policy in the context of limited financial resources and their irrational use does not contribute to the effective development and reproduction of human potential in accordance with the needs of the digital economy. Despite the nominal increase in social spending, their structure is irrational, and the spending itself do not consider as investment. An insufficient level of investment activity in the field of investment in human capital observe at the corporate and individual levels. It has been determined that the main incentive for the development of human capital affects the formation of a motivational basis at all levels is the purposeful, consistent and pragmatic activity of state authorities aimed at implementing a certain development strategy for the country, ensuring its security and macroeconomic stability. An important condition is also the creation of a regulatory framework that is adapted to the specifics and realities of economic and social transformations in the context of digitalization, the regulation of labor relations, and the preservation of social and investment guarantees. To regulate and intensify investment activities, a model of investment support for the human capital development is proposed. It involves the redistribution of investment resources in accordance with the subjects of investment and the expected results of the investment process, forms and criteria for assessing individual components of human capital at different stages of the life cycle, together form a general model of financing it development and reproduction at all levels.